Development of Scientific Literacy Test Instruments for Ecotourism-Based Field Practicum Students Prospective Biology Teachers - Yamin, Muhammad; Jufri, A Wahab; Hakim, Aliefman; Gunawan, Gunawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This development research aims to assess the validity and reliability of scientific literacy measurement instruments based on bird ecotourism that are feasible, effective, practical, and receive positive student responses. The research design uses the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data was collected using Observation, interview, test, questionnaire, and documentation methods. Data analysis was carried out quantitatively on scientific literacy measurement instruments' validity, reliability, and practicality by calculating the average score and determining the criteria at certain class intervals. The results show that the scientific literacy measurement instrument is valid, reliable, and effective in improving the scientific literacy of prospective science-biology teacher students, so it is suitable for use in learning. The reliability of the scientific literacy skills (SLS) test is 0.94 (very good). The N-gain value for the SLS post-test in the experimental class was 71, while the N-gain value for the control class post-test was 63. The difference test results using the Mann-Whitney test were obtained from Asymp. Sig. 0.038 ≤ 0.05. This means there is a significant increase in the ability of experimental class students to SLS after learning activities. Student responses to EBFP-M were recorded as 24 people (86%) giving positive assessments (good and very good), and the implementation of 13 aspects (81%) of the 16 aspects measured was good.